Antiproliferative potential of Plinia edulis leaves - Ishikawa, Tati; Yamaguchi, Lydia Fumiko; Barros, Silvia Berlanga de Moraes; Rodas, Andrea Cecilia Dorión; Higa, Olga Zazuco; Ruiz, Ana Lúcia Tasca Gois; Varanda, Eliana Aparecida; Kato, Edna Tomiko Myiake (Acta Scientiarum. Biological Sciences, 2024)
Plinia edulis, popularly known as ‘cambucá’, is used in Brazilian folk medicine to treat several conditions. The aim of this study was to evaluate the mutagenicity and cytotoxicity of cambucá leaf extract, as well as its antioxidant activity. The ‘Ames’ test and Orac assay were used to evaluate the mutagenicity and antioxidant activity, respectively, and the phytochemical analysis of the ethanol leaf extract (LE) was performed by chromatographic and spectrometric methods. The in vitro cytotoxicity was tested on CHO (Chinese Hamster Ovary) cells and on nine human tumor cell lines. Phytochemical analysis of LE has revealed the presence of triterpenes and flavonoids. The LE did not show mutagenicity at the concentration of 20 mg plate-1 and exhibited high antioxidant activity, with Orac value of 3948 µmol TE g-1. The LE and its fractions (ethyl acetate; methanol) showed antiproliferative activity against cancer cell lines and proliferative activity in normal cells. The ethyl acetate fraction was the most active extract, presenting antiproliferative activity against strains of breast cancer, prostate cancer, colon cancer, lung cancer, melanoma and leukemia (GI50 0.01-8.57 µg mL-1), being more effective than the reference drug (doxorubicin) against human breast adenocarcinoma MCF-7 cell line. These results suggest P. edulis as a potential adjuvant in cancer therapy and chemoprevention.